Effect of nifedipine on serum theophylline concentrations and asthma control. Issue 10 (October 1987) - Smith, S R; Wiggins, J; Stableforth, D E; Skinner, C; Kendall, M J
Abstract : The effect of adding slow release nifedipine to oral theophylline has been studied in eight patients with stable but symptomatic asthma, a double blind placebo controlled crossover protocol being used. No change in asthma control occurred during the nifedipine treatment period as assessed by serial peak flow measurements and symptom scores. Serum theophylline concentrations were significantly lower after nifedipine than after placebo (6.8 v 9.7 micrograms/ml) and in three patients were well below the therapeutic range (less than 4 micrograms/ml).